Comparative Performance in Single-Port Versus Multiport Minimally Invasive Surgery, and Small Versus Large Operative Working Spaces: A Preclinical Randomized Crossover Trial - Marcus,HJ; Seneci,CA; Hughes-Hallett,A; Cundy,TP; Nandi,D; Yang,GZ; Darzi,A (Surgical Innovation, 2016)
Background. Surgical approaches such as transanal endoscopic microsurgery, which utilize small operative working spaces, and are necessarily single-port, are particularly demanding with standard instruments and have not been widely adopted. The aim of this study was to compare simultaneously surgical performance in single-port versus multiport approaches, and small versus large working spaces. Methods. Ten novice, 4 intermediate, and 1 expert surgeons were recruited from a university hospital. A preclinical randomized crossover study design was implemented, comparing performance under the following conditions: (1) multiport approach and large working space, (2) multiport approach and intermediate working space, (3) single-port approach and large working space, (4) single-port approach and intermediate working space, and (5) single-port approach and small working space. In each case, participants performed a peg transfer and pattern cutting tasks, and each task repetition was scored. Results. Intermediate and expert surgeons performed significantly better than novices in all conditions (P < .05). Performance in single-port surgery was significantly worse than multiport surgery (P < .01). In multiport surgery, there was a nonsignificant trend toward worsened performance in the intermediate versus large working space. In single-port surgery, there was a converse trend; performances in the intermediate and small working spaces were significantly better than in the large working space. Conclusions. Single-port approaches were significantly more technically challenging than multiport approaches, possibly reflecting loss of instrument triangulation. Surprisingly, in single-port approaches, in which triangulation was no longer a factor, performance in large working spaces was worse than in intermediate and small working spaces.